THE INFLUENCE OF KAIZEN CULTURE AND THE WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Rafiah Khaerunnisa; Haedar Haedar; Hadi Pajarianto (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
The purpose of this study is to investigate how the work environment and kaizen culture affect employee performance. Credit Plus staff were given questionnaires to complete in order to gather data for the study, which takes a quantitative approach. Probability sampling is the sampling method used, which guarantees that every member of the population has an equal chance of being chosen for the sample. There were 115 responders in the trial. The results show that while the work environment has a considerable impact on employee performance, kaizen culture has no discernible effect on it. Additionally, it has been demonstrated that kaizen culture and the workplace have a favorable and significant impact on employee performance when examined concurrently.